The Predictive Validity of Three Youth Violence Assessment Instruments: The SAVRY, VRS-YV, and SAPROF-YV - Koh, Li Lian (International journal of offender therapy and comparative criminology, 2022)
This study examined the predictive validity of three assessment instruments for violent youth, the SAVRY, the VRS-YV, and the SAPROF-YV. Files relating to a sample of 233 young male offenders aged between 12 and 18 years were retrospectively reviewed to score each instrument, with reoffending data extracted from prison, community and juvenile justice records. The analysis showed that all three assessments predicted general (any) reoffending better than violent and non-violent reoffending, with higher rates of predictive validity for the SAVRY and VRS-YV Total Scores. There were, however, only small to moderate effect sizes at 1- and 3-year follow up periods for all three instruments in predicting all types of reoffending. The SAPROF-YV had a small effect size for the prediction of violent reoffending and did not add incrementally to the predictive validity (for violent reoffending) of the SAVRY or VRS-YV.